Improvement of jaw crushers reliability using elastic pneumatic elements in the connection of kinematic pairs; IOP Conference Series: Materials Science and Engineering; Vol. 411 : Metallurgy: Technologies, Innovation, Quality. Metallurgy-2017 - Nikitin A. G.; Abramov A. V.; Zhivago E. Ya.; Dvornikov L. T.; Saruev L. A. Lev Alekseevich (Papers, 2018)
Title screen